Fabrication and evaluation of poly(ε-caprolactone) based nanofibrous scaffolds loaded with homoeopathic mother tincture of Syzygium cumini for wound healing applications - Deiviga Murugan; Ankitha Suresh; Goutam Thakur; Bhisham Narayan Singh (Elsevier, 2023)
Traditional wound healing substitutes loaded with bioactive molecules such as drugs, growth factors, and so on have been extensively researched in order to promote better wound healing and restore normal tissue function. The use of nanofibrous scaffolds has enhanced the biomaterial performance, thereby offering a promising solution as wound dressings in the field of skin tissue engineering. In the present study, the homoeopathic mother tincture extract of Syzygium cumini incorporated in poly(ε-caprolactone) nanofibrous scaffolds were fabricated in the concentration range of 5 %-20 % (w/w) and its various physicochemical and biological properties were evaluated. The fabricated nanofibers structurally mimicked the extracellular matrix, with enhanced hydrophilicity for better cellular attachment and proliferation. These scaffolds also showed anti-biofilm activity against P. aeruginosa and S. aureus and exhibited superior anti-oxidant activity. Furthermore, the extract incorporation was observed to be beneficial in cell adhesion, viability, growth and proliferation. This novel poly(ε-caprolactone) nanofibrous scaffold loaded with homoeopathic mother tincture  extract of Syzygium cumini might be a suitable biomaterial for clinical management of wounds and reconstruction of damaged/diseased skin tissues.